A Treg-Selective IL-2 Mutein Prevents the Formation of Factor VIII Inhibitors in Hemophilia Mice Treated With Factor VIII Gene Therapy - Chen, Alex C.; Cai, Xiaohe; Li, Chong; Khoryati, Liliane; Gavin, Marc A.; Miao, Carol H. (Frontiers in Immunology, 2020)
Hemophilia A is a genetic disorder that results in the deficiency of functional factor VIII protein, which plays a key role in blood coagulation. Currently, the majority of hemophilia A patients are treated with repeated infusions of factor VIII protein. Approximately 30% of severe hemophilia A patients develop neutralizing antibodies to factor VIII (known as factor VIII inhibitors) due to treatment, rendering factor VIII protein infusions ineffective. Previously, mice receiving murine IL-2 complexed with α-murine IL-2 mAbs showed a lack of factor VIII inhibitor formation after factor VIII treatment, which was associated with proliferation and activation of factor VIII-specific regulatory T cells. In this paper, we evaluated if an Fc-fused mutated protein analogue of mouse IL-2, named Fc.Mut24, engineered to selectively promote expansion of regulatory T cells in vivo can modulate factor VIII-specific immune responses. Mice received one intraperitoneal injection of Fc.Mut24. When the regulatory T cell population reached its highest frequency and peak activation, mice received a hydrodynamic injection of factor VIII plasmid (Day 4) followed by a second Fc.Mut24 dose (Day 7). Peripheral blood was collected weekly; flow cytometry was used to characterize peripheral blood cell populations, while ELISA and Bethesda assays were used to assess inhibitor concentrations and functional titers in plasma. aPTT was used to assess functional activities of factor VIII in blood. Mice receiving Fc.Mut24 showed a dramatic and transient increase in activated regulatory T cell population after Fc.Mut24 injection. Factor VIII gene therapy via hydrodynamic injection resulted in high anti-factor VIII inhibitor concentrations in control PBS-injected mice, whereas mice treated with Fc.Mut24 produced no inhibitors. Most significantly, no inhibitors were generated after a second hydrodynamic injection of factor VIII plasmid administered 19 weeks after the first injection in Fc.Mut24 treated mice. Mice receiving Fc.Mut24 maintained high levels of factor VIII activity throughout the experiment, while control mice had factor VIII activity drop to undetectable levels a few weeks after the first factor VIII plasmid injection. Our data show that human therapies analogous to Fc.Mut24 could potentially provide a method to prevent inhibitor formation and induce long-term immune tolerance to factor VIII in hemophilia patients.